CORRELATION BETWEEN CERVICAL LENGTH WITH SUCCESSFUL LABOR INDUCTION - Tendean, Hermie M. M. (UNIVERSITAS SAM RATULANGI, 2015)
Objective : To determine the correlation between cervical length on transvaginal ultrasound assessment with successful labor induction. Method : This was an observational study with crosssectional approach to 39 consecutive women who undergoing induction of labor in the Department of Obstetrics and Gynecology, Prof. dr. R.D. Kandou Manado general hospital. Cervical length was measured by transvaginal ultrasound prior to induction of labor. Labor induction were success if vaginal delivery occured within 24 hours after induction of labor began. Results:Induction of labor succeed in 34 subjects (87.18%) with a mean of cervical length 2,60 + 0,43 cm and failed in 5 subjects (12.82%) with a mean of cervical length of 3,54 + 0,77 cm (p = 0.006). The optimal cut off point for predicting the success of labor induction was 2,895 cm. Cervical length ≤ 2,895 cm had a sensitivity of 79,41% and a specificity of 80,00%, positive predictive value of 93,10%, negative predictive value of 36,63% andaccuracy of 79,49%. Conclusion: There was a significant correlation between cervical length with the successful induction of labor, cervical length ≤ 2.895 cm can be used to predict the success of labor induction. Keywords: Induction of Labor, Cevical Length, Transvaginal Ultrasound